2006
DOI: 10.2478/s11696-006-0071-3
|View full text |Cite
|
Sign up to set email alerts
|

Citric acid production from raw glycerol by acetate mutants of Yarrowia lipolytica

Abstract: Three acetate mutants of the yeast species Yarrowia lipolytica were screened using batch cultivation. The strain Y. lipolytica 1.31 was found to be the most suitable for citric acid production from raw glycerol, a by-product of biodiesel production from rapeseed oil. At the initial concentration of glycerol of 200 g dm−3, the citric acid production of 124.5 g dm−3, yield of 0.62 g g−1, and productivity of 0.88 g dm−3 h−1 were achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 1 publication
7
72
0
5
Order By: Relevance
“…A. niger are principally used to produce citric acid, however in culturing these fungi, the growth of Aspergillus in pellet form is desirable and this can be achieved by process optimization [5,6]. Yarrowia lipolytica has the ability to produce citric acid from raw glycerol [7], a by-product of biodiesel production from rapeseed oil. Citric acid is produced commercially employing various inexpensive and readily available raw materials like molasses, carob pod extract, rape seed oil, corn-cobs, apple and grape pomace, kiwi-fruit peel, mandarine orange and brewery wastes have been used as carbon substrates [8] in terrestrial environment.…”
Section: Introductionmentioning
confidence: 99%
“…A. niger are principally used to produce citric acid, however in culturing these fungi, the growth of Aspergillus in pellet form is desirable and this can be achieved by process optimization [5,6]. Yarrowia lipolytica has the ability to produce citric acid from raw glycerol [7], a by-product of biodiesel production from rapeseed oil. Citric acid is produced commercially employing various inexpensive and readily available raw materials like molasses, carob pod extract, rape seed oil, corn-cobs, apple and grape pomace, kiwi-fruit peel, mandarine orange and brewery wastes have been used as carbon substrates [8] in terrestrial environment.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol may be used as carbon source in many bioprocesses, and one promising exploitation is to produce 1,3-PDO by Klebsiella pneumoniae and Clostridium butyricum (Papanikolaou and Aggelis, 2009;Rymowicz et al, 2006). Production from crude glycerol from biodiesel can contribute to the reduction of environmental pollution and commercial valorization of this carbon source and to lower the production of 1,3-propanediol.…”
Section: Introductionmentioning
confidence: 99%
“…54 321 Accordingly, higher glycerol above 60 g/L is responsible to induce higher osmotic pressure 322 which could inhibit the oxygen uptake or create high osmotic pressure sufficient to inhibit 323 culture growth in other strains. 18 More often, Rymowicz et al (2006) have 328 17 found that Y. lipolytica mutants can be cultivated in the presence of raw glycerol at extremely 329 high concentrations (i.e. 200 g/L) and can achieve efficient cell growth ranging from 16.5-330 26.5 g/L.…”
Section: Optimization Study 154mentioning
confidence: 99%